ANALISIS EFEKTIVITAS MODEL PRODUKSI FILM ANIMASI CERITA RAKYAT BABAD BATURRADEN BERBASIS ARTIFICIAL INTELLIGENCE SEBAGAI UPAYA DIGITALISASI DAN PELESTARIAN BUDAYA LOKAL - DEUIS NUR ASTRIDA (LPPM Universitas Abdurrab, 2026)
Folklore represent an important form of intangible cultural heritage containing historical, philosophical, and educational values that contribute to cultural identity formation. However, the rapid advancement of digital technology has reduced younger generations' interest in traditional narrative media. This study aims to analyze the effectiveness of an Artificial Intelligence (AI)-based animation film production model for the folklore Babad Baturraden as an effort to support cultural digitalization and preservation. The study employed an applied research approach using the Research and Development (R&D) method adopting the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The production process was conducted from February to April 2026 using ChatGPT for scriptwriting and storyboard development, Google Flow for visual asset creation and animation production, and Suno AI for music generation. The resulting animation film has a duration of 25 minutes and 44 seconds, consisting of 18 scenes, 24 sequences, and 111 shots. The results indicate that the AI-based production model improved production time efficiency by 64.8%, reduced human resource requirements by 70%, and decreased production costs by 80% compared to conventional production methods. Multimedia expert validation achieved an average score of 4.67, cultural validation obtained an average score of 4.73, and user satisfaction evaluation reached an average score of 4.68, all categorized as excellent. Furthermore, the System Usability Scale (SUS) evaluation produced an average score of 85.4, categorized as excellent. The findings demonstrate that the AI-based animation production model is effective as a strategy for digitalization and preservation of local cultural heritage through animation media.